Case Report: Laryngotracheal Post-Intubation/Tracheostomy Stenosis in COVID-19 Patients - Onorati, Ilaria; Bonnet, Nicolas; Radu, Dana Mihaela; Freynet, Olivia; Guiraudet, Patrice; Kambouchner, Marianne; Uzunhan, Yurdagul; Zogheib, Elie; Martinod, Emmanuel (Frontiers in Surgery, 2022)
Introduction The novel Coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV-2), has spread rapidly to become a major global public health emergency since March 2020. Laryngotracheal stenosis (LTS) has been observed more frequently since the onset of the COVID-19 pandemic. Methods All patients referred to our 24/7 Airway Diseases Center for laryngotracheal post-intubation/tracheostomy stenosis from May 2020 to May 2021were evaluated retrospectively. Patient data on comorbidities, diagnosis, type of procedures, lengths of ICU stay and invasive mechanical ventilation, medical treatment, and the severity of illness were recorded. Results This case series included nine patients (five women and four men), with a mean age of 52.9 years, most with a BMI >30, all with a severe illness revealed by the Simplified Acute Physiology Score (SAPS) II >31. From May 2020 to May 2021, 21 procedures were performed on seven patients, consisting of bronchoscopic rigid interventions, T-tube Montgomery tracheostomy, and one cricotracheal resection with end-to-end anastomosis. Histologic examination of tracheal biopsies showed an inflammatory state of the airway mucosa. Two patients only had medical therapy. Discussion and Conclusions Pneumonia caused by SARSCoV-2 can lead to severe acute respiratory distress syndrome (ARDS) requiring invasive mechanical ventilation. The time of intubation, the drugs used, the prone position, comorbidities (diabetes, obesity), and the inflammatory state of the upper airways linked to the viral infection, predispose to an increased tendency to stenosis and its recurrence. A conservative approach with medical and endoscopic treatment should be preferred in case of persistence of local airways inflammation. Further studies with a larger sample of patients will help to a better understanding of the disease, reduce the prevalence, and improve its treatment.